The Integration Duolingo as a Technology-Based Approach to Improve Students’ Motivation and Vocabulary Skills at SMP ISLAM YUHA Cempaka Putih - Nadia Ningsih; Ahmad Syukron Siddik; Hamjah Hamjah (Tirai Edukasi : Jurnal Pendidikan, 2025)
This study investigates the effectiveness of integrating Duolingo as a technology-based approach to enhance the learning motivation and vocabulary mastery of seventh-grade students at SMP Islam YUHA Cempaka Putih. Employing a quantitative method, the research adopted a pre-experimental one-group pre-test and post-test design. A purposive sample of 22 students participated in the study. Data were collected using a vocabulary test and a motivation questionnaire, both administered before and after the treatment. The findings revealed a significant improvement in students’ motivation, with mean scores rising from 17.09 (pre-test) to 33.50 (post-test). Similarly, vocabulary mastery scores improved from 38.86 to 68.64. A paired sample t-test confirmed the significance of these results (p < 0.05), leading to the rejection of the null hypothesis. These findings demonstrate that Duolingo is an effective technological tool to improve students’ motivation and vocabulary acquisition.